PARP Inhibitors in Patients With Newly Diagnosed Advanced Ovarian Cancer: A Meta-Analysis of Randomized Clinical Trials - Wang, Yizi; Ren, Fang; Song, Zixuan; Wang, Xiaoying; Zhang, Chiyuan; Ouyang, Ling (Frontiers in Oncology, 2020)
Background: The efficacy of poly (adenosine diphosphate–ribose) polymerase inhibitors (PARPis) as a maintenance therapy in patients with newly diagnosed advanced ovarian cancer remains unclear. We conducted a meta-analysis to assess the benefits and safety of PARPis maintenance therapy in patients with newly diagnosed advanced ovarian cancer. Methods: We searched the PubMed, Embase, and Cochrane databases for randomized control trials (RCTs) which assessed the efficacy of PARPis as a maintenance therapy for newly diagnosed advanced ovarian cancer. Progression-free survival (PFS) was the primary endpoint, which was assessed using hazard ratios (HRs) with 95% confidence intervals (95% CI). PFS was extracted independently, and the pooled results were used to compare the prognoses of patients who received PARPis maintenance therapy and those who received a placebo. Results: Three RCTs, SOLO1, VELIA/GOG-3005 and PRIMA, which included 1,881 patients with newly diagnosed advanced ovarian cancer, were included in the meta-analysis. The overall analysis showed that PARPis maintenance therapy signiﬁcantly increased PFS (HR 0.51, 95% CI 0.33–0.80, P = 0.004) compared to placebo. Subgroup analyses confirmed this result. We also observed an improved PFS in patients with homologous-recombination deficiency (HRD) (HR 0.50, 95% CI 0.38–0.66, P < 0.001) and in patients with BRCA mutations (HR 0.42, 95% CI 0.31–0.57, P < 0.001). Moreover, there were no significant differences in health-related quality of life between the PARPis and placebo groups. Conclusions: Patients with newly diagnosed advanced ovarian cancer who received PARPis maintenance therapy had a better prognosis than those who received a placebo. Moreover, no significant changes in health-related quality of life were seen in PARPis-treated individuals.